Letter from James Curtis Booth to Miss Hannah Scott - Booth, James Curtis (1883)
James Curtis Booth (1810-1888) writes to Miss Hannah Scott, a family friend, to thank her for her gift of a bottle of water from Richland Springs.
Keywords: Booth, James Curtis, 1810-1888; Texas--Richland Springs